PENGARUH JUMLAH MATA TUNAS TERHADAP PERTUMBUHAN STEK BATANG TRUBUSAN SUNGKAI (Peronema canescens) - Indri Elang Mayanti; Basir Achmad (Jurnal Sylva Scienteae, 2021)
The areas of tropical forests in Indonesia always decrease every year, so that efforts are needed to cultivate plants efficiently for the supply of seedlings. Sungkai (Peronema canescens) has good quality wood that can be used for various purposes, either for construction, furniture, plywood or the leaves can be used for medicine. The purpose of this study was to analyze the growth of stem cuttings of sungkai based on the number of latent buds by calculating the root dry weight, bud dry weight, and total dry weight. This study used a factorial complete randomized design. There were two factors studied, namely the number of buds consisting of 2 levels: 2 buds and 1 bud, and the stem split factor. Each treatment was replicated 3 times and each experiment unit used 5 cuttings. The growth of sungkai cuttings in the treatment of two buds had a total dry weight of 170.04 grams, while the treatment of one bud had a total dry weight of 98.30 grams. The results of this study indicated that the more the number of latent buds, the more root and bud growth of cuttings.Keywords: Coppice; Latent buds; Cuttings; Sungkai